2019
DOI: 10.1158/2326-6066.cir-18-0494
|View full text |Cite
|
Sign up to set email alerts
|

Activated Eosinophils Exert Antitumorigenic Activities in Colorectal Cancer

Abstract: Immunotherapies targeting T lymphocytes are revolutionizing cancer therapy but only benefit a subset of patients, especially in colorectal cancer. Thus, additional insight into the tumor microenvironment (TME) is required. Eosinophils are bone marrow–derived cells that have been largely studied in the context of allergic diseases and parasite infections. Although tumor-associated eosinophilia has been described in various solid tumors including colorectal cancer, knowledge is still missing regarding eosinophil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
138
2
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 138 publications
(150 citation statements)
references
References 48 publications
9
138
2
1
Order By: Relevance
“…36,37 In mouse models of colorectal cancer, where IFN-γ is increased, eosinophils directly kill tumors independent of CD8 + T cell functions. 38 This supports findings in colorectal patients where eosinophils correlate with better prognosis and fewer metastases. 39 Alternatively, in melanoma CD8 + T cell recruitment is enhanced by IFN-γ and tumor necrosis factor α (TNF-α) activated eosinophils, resulting in melanoma tumor killing.…”
Section: Eos Inophil S In C An Cersupporting
confidence: 85%
See 1 more Smart Citation
“…36,37 In mouse models of colorectal cancer, where IFN-γ is increased, eosinophils directly kill tumors independent of CD8 + T cell functions. 38 This supports findings in colorectal patients where eosinophils correlate with better prognosis and fewer metastases. 39 Alternatively, in melanoma CD8 + T cell recruitment is enhanced by IFN-γ and tumor necrosis factor α (TNF-α) activated eosinophils, resulting in melanoma tumor killing.…”
Section: Eos Inophil S In C An Cersupporting
confidence: 85%
“…For example, in oral squamous cell carcinoma, it has been proposed that early‐stage carcinoma, which is a Th1‐type microenvironment, leads to anti‐tumorigenic activation of eosinophils while later stages of carcinoma develop a Th2‐type microenvironment and promote pro‐tumorigenic potential of eosinophils . In mouse models of colorectal cancer, where IFN‐γ is increased, eosinophils directly kill tumors independent of CD8 + T cell functions . This supports findings in colorectal patients where eosinophils correlate with better prognosis and fewer metastases .…”
Section: Eosinophils In Cancersupporting
confidence: 59%
“…39 Furthermore, it has been recently demonstrated an IFN-γ-linked signature in eosinophils infiltrating mouse colorectal tumors and showing a strong anti-tumor activity. 40 IL-2 has been demonstrated to be upregulated in a melanoma mouse model after treatment with ICI 41 and in patients responding to CTLA-4 inhibition. 42 Our GSEA results suggest that eosinophils could be influenced by cytokines released during ICI treatment.…”
Section: Discussionmentioning
confidence: 98%
“…First, there have been no reports of a distinctive syndrome or health failure across several eosinophil-deficient mice strains under ordinary laboratory conditions [69,[76][77][78]. While some studies have reported that eosinophils have no tumoricidal activity [79,80], preclinical models of inducible or transplantable tumors have suggested a role for eosinophils in tumor regression and an increase in tumor incidence in the absence of eosinophils [81][82][83]. Other preclinical studies have examined the potential mechanisms linking eosinophils to cancer, with a particular focus on IL-5.…”
Section: Eosinophils In Malignanciesmentioning
confidence: 99%